State of the art and new directions using DNA and other molecular markers in forensic entomology - David Haymer (Academia Biology)
In parallel with the entire field of forensic science, forensic entomology has been dramatically transformed through the incorporation of DNA and other molecular markers into its practices. Beginning with the use of single mitochondrial genes, the range of DNA-based markers available to forensic entomologists has grown to include a wide variety of individual mitochondrial and nuclear genes, and has further expanded to include the analysis of whole genomes and transcriptomes. The use of these new sets of markers has significantly enhanced the ability of forensic entomologists to identify insects associated with human cadavers and to provide improved estimates of the time elapsed since death, commonly referred to as the postmortem interval (PMI), along with other valuable information for crime scene investigations. Furthermore, as new types of DNA markers and methods, including those based on epigenetic phenomena, continue to be developed for human and other forensic applications, the incorporation of these new technologies into forensic entomology will further enhance the capacity of professionals in this field to provide timely and valuable information to crime investigators.